Susceptibility of Flowers and Bedding Plants to Root-Knot Nematodes - Romy Krueger; Robert McSorley (EDIS)
ENY-061, a 7-page illustrated fact sheet by Romy Krueger and Robert McSorley, summarizes recently published work on varying plant susceptibilities to root-knot nematodes and provides an overview of flower cultivars and their susceptibility to different species and races of root-knot nematodes, particularly M. incognita, M. javanica, and M. arenaria, all of which are common in Florida. Includes references. Published by the UF Department of Entomology and Nematology, May 2010.